Consumo e cidadania na “nova classe média” - Natacci, Renata de Carvalho (2019)
The goal of this academic study is to discuss the relationship between citizenship and consumption in Brazil in the years 2000, more specifically in the context of an emerging social stratum known as “new middle class”. It is this study`s intention to understand whether income increase – with possible consumption increase – made people of that social strata modify their relationship with the State. In order to reach this objective, at first it is discussed the concept of citizenship, mainly according to T. H. Marshall, its implementation and evolution in the country according to José Murilo de Carvalho and its connections with consumption. Moving ahead, this academic work sheds light on the “new middle class”, covering themes like how the economic scenario enabled the rising of a discourse about this “new” class, the elaboration and definition of an official criteria to identify its members (criteria developed by the Secretaria de Assuntos Estratégicos da Presidência da República), also the characterization of this class as done by the official sources and the debate revolving around the setting of this criteria among the academic environment. As a way to obtain an empiric answer to this study main question – whether income and consumption increase can transform the citizen`s relationship with the state – an analysis is performed on data from ESEB (Estudo Eleitoral Brasileiro) dataset, based on selected questions from the available four waves of their research (2002, 2006, 2010 e 2104). This analysis shows that it is not possible to conclude there is a relationship between income and consumption increase and a change of perception about the State and its institutions. In the period analyzed, based on what is known about Brazilian political cultural, other factors seem to be more relevant to explain the results seen in the ESEB’s surveys